The PENGARUH PROFITABILITAS, LIKUIDITAS, DAN RISIKO SISTEMATIS TERHADAP RETURN SAHAM PERUSAHAAN LQ45 TAHUN 2015-2019 - Milka Terutama (Bina Ekonomi, 2021)
The purpose of investing in stocks is to get return in the form of capital gain and dividend. Before making an investment decision, investors and potential investors are expected to make an analysis. One of the analysis that can be done is fundamental analysis, financial reports is one of the most important source to do fundamental analysis. From financial reports, investors and potential investors can assess company’s profitability and liquidity. In addition to return, investors and potential investors have to consider risks. Risk that arises from factors that are external to the organization is called systematic risk. The population used in this study is companies listed in LQ45 year 2015-2019. The sampling technique used is purposive sampling technique in order to obtain 25 samples of companies that met the research criteria. The type of data used is secondary data in the form of financial reports accessed through companies’ websites, stock prices and dividends from Yahoo Finance, journals, and literature books. The data processing and analysis techniques used in this study are statistic descriptive, classical assumption tests, hypothesis testing which includes the t statistical test and F statistical test. The results showed that partially, the variables of profitability, liquidity, and systematic risk cannot be stated to have an effect on stock return. Simultaneously, the variables of profitability, liquidity, and systematic risk cannot be stated to have an effect on stock return.   Keywords: profitability, liquidity, systematic risk, stock return, LQ45.